OXIDATIVE STRESS–MEDIATED MODULATION OF THE MONOOXYGENASE SYSTEM: IMPLICATIONS FOR XENOBIOTIC BIOTRANSFORMATION - Mamazulunov, Nurmuhammad (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This study investigates how oxidative stress modulates the structure and function of the hepatic microsomal monooxygenase system and consequently alters xenobiotic biotransformation. Oxidative imbalance was experimentally induced in vivo (Wistar rats) and in vitro (HepG2 cells) using mechanistically distinct oxidants, including hydrogen peroxide, paraquat, and alloxan. Comprehensive biochemical, proteomic, and enzymatic assays were employed to quantify reactive oxygen species (ROS) generation, lipid peroxidation, protein carbonylation, antioxidant enzyme responses, and the functional integrity of cytochrome P450 (CYP) isoforms, NADPH–cytochrome P450 reductase (CPR), and cytochrome b₅. Oxidative stress significantly elevated ROS, malondialdehyde, and protein carbonyl levels, confirming pronounced molecular damage. CYP1A2 and CYP2E1 expression and activity were markedly upregulated, whereas CYP3A4 and CYP2D6 exhibited moderate downregulation at both mRNA and protein levels. CPR activity increased without changes in substrate affinity, indicating enhanced electron transfer capacity under oxidative strain. Functional probe assays demonstrated increased CYP1A2- and CYP2E1-mediated monooxygenase activities, accompanied by reduced CYP3A4-dependent metabolism. Correlation analyses revealed strong positive associations between oxidative biomarkers and CYP2E1 induction, while CYP3A4 suppression correlated with protein oxidation. Phenotype-specific evaluations showed slow metabolizers to be more susceptible to oxidative induction of CYP2E1 and CPR than fast metabolizers. Collectively, the findings elucidate multi-level regulatory mechanisms through which oxidative stress reshapes monooxygenase system architecture, alters coupling efficiency, shifts detoxification versus bioactivation balance, and ultimately modifies xenobiotic metabolic fate. These insights enhance mechanistic understanding of redox-driven variability in drug metabolism, toxic responses, and disease-associated metabolic dysfunction.